Penggunaan Suntik Putih di MD Clinic Makassar; Tinjauan Hukum Islam - Nurhayanti (Universitas Islam Negeri Alauddin Makassar, 2022)
The main problem of this research is how to use, white injection at MD Clinic Makassar? Then it is translated into several sub-problems, namely: 1) What is the content and process of implementing white injection at MD Clinic Makassar? 2) How is Islamic law reviewing the use of white injection at MD Clinic Makassar?. This type of research is classified as qualitative with research approach used is sociological juridical. The data sources for this research are primary and secondary data. This research is classified as a research with qualitative data types, namely by processing primary data sourced from interviews with employees and white injection users at MD Clinic Makassar. The results showed than 1) the content used at MD Clinic Makassar is safe to use and the implementation process is quite safe because it is carried out by doctors and nurses who are experts in their fields. 2) According to a review of Islamic law, the use of white injection at the MD Clinic Makassar, which is seen from the content used and the safe and halal implementation process, can be done if it is to cure disease. But white injection are used for beauty purposes, then the law becomes haram. White injection is an act ofself-harm, and the act of changing Allah’s creation by changing the original skin to be brighter. The act of white injection is also an act of not being grateful for the gift of Allah swt. The implication of this research is need for knowledge before giving white injection to the content and dosage that will be used for white injection and knowig how to process is safe or not. It’s very important to know the content tobe injected into the body so as not to cause effects and dangers for white injection users